Household finance and consumption survey in Malta: the results from the second Wave - Daniel Gaskin; Juergen Attard; Karen Caruana (Central Bank of Malta, 2017)
This report presents salient results from the second wave of the Household Finance and Consumption Survey for Malta which is part of a co-ordinated statistics and research project led by the European Central Bank.
Keywords: D1; D3; 330